Information Systems and Developing Countries: Failure, Success, and Lo cal Improvisations - Heeks, Richard (The Information Society, 2002)
This article presents evidence that–alongside the successes– many info rmation systems in developing countries can be categorized as failing either totally or partially. It then develops a new model that seeks t o explain the high rates of failure. The model draws on contingency th eory in order to advance the notion of design-actuality gaps: the matc h or mismatch between IS designs and local user actuality. This helps identify two high-risk archetypes that affect IS in developing countri es: country context gaps and hard-soft gaps. The model is also of valu e in explaining the constraints that exist to local IS improvisations in developing countries. Overall, the article shows how model and theo ry help understand IS cases in developing countries, and equally, how those cases provide valuable data to help develop IS models and theori es.
Keywords: Developing Country; Evaluation; Failure; Information System; implementation